Asthma and dietary intake: an overview of systematic reviews. Issue 4 (19th January 2016) - Garcia‐Larsen, V.; Del Giacco, S. R.; Moreira, A.; Bonini, M.; Charles, D.; Reeves, T.; Carlsen, K.‐H.; Haahtela, T.; Bonini, S.; Fonseca, J.; Agache, I.; Papadopoulos, N. G.; et al.
Abstract: Epidemiological research on the relationship between diet and asthma has increased in the last decade. Several components found in foods have been proposed to have a series of antioxidant, anti‐allergic and anti‐inflammatory properties, which can have a protective effect against asthma risk. Several literature reviews and critical appraisals have been published to summarize the existing evidence in this field. In the context of this EAACI Lifestyle and asthma Task Force, we summarize the evidence from existing systematic reviews on dietary intake and asthma, using the PRISMA guidelines. We therefore report the quality of eligible systematic reviews and summarize the results of those with an AMSTAR score ≥32. The GRADE approach is used to assess the overall quality of the existing evidence. This overview is centred on systematic reviews of nutritional components provided in the diet only, as a way to establish what type of advice can be given in clinical practice and to the general population on dietary habits and asthma.